Ceramic filter tube catalyst as well as preparation method and application thereof

By raising the pH value of the carrier and the active component on the ceramic filter pipe, and using a decentralist and surfactant, the uniform distribution of the active component on the carrier is realized, solving the uneven distribution of active components in existing technologies in existing technologies The problem improves the activity and service life of catalysts.

CN119368164APending Publication Date: 2025-01-28MCC CAPITAL ENGINEERING & RESEARCH INC LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310931727.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

Existing ceramic catalysts cannot ensure the uniform distribution of active components on the support, resulting in agglomeration and uneven catalytic activity.

Method used

By adjusting the pH value of the carrier and the active component, it is evenly distributed on the ceramic filter pipe. The cooperation of the dispersant and the surfactant is used to achieve the high decentralized and single layer coverage of the active component.

Benefits of technology

The uniform distribution of catalytic components on the carrier, reducing the phenomenon of gathering, reducing the amount of catalytic components, and increasing the activity and service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004361878220000071
    Figure BDA0004361878220000071
Patent Text Reader

Abstract

The invention discloses a ceramic filter tube catalyst as well as a preparation method and application thereof. The preparation method comprises the following steps: adding a carrier into water, adding a precursor of an active component while stirring, and continuously stirring to obtain a mixture; adding acid to adjust the pH value of the mixture to 4.0-4.5, and then adding a dispersing agent to adjust the pH value to 8.5-9.5; grinding the mixture until the D50 particle size of the mixture is 40-300nm, and then diluting the mixture with a dispersing agent solution to obtain diluted steeping liquor; soaking a ceramic filter tube in the diluted steeping liquor, and then drying and roasting to obtain the ceramic filter tube catalyst. The ceramic filter tube catalyst disclosed by the invention has a nitrogen oxide selective catalytic reduction (SCR) function, the preparation method is novel and simple to implement, uniform distribution of catalytic components on a carrier layer is realized by regulating and controlling pH, the dosage of catalytic active components is reduced, and the use cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of environmental protection materials, and in particular to a ceramic filter tube catalyst and a preparation method and application thereof, and more particularly to a ceramic filter tube catalyst for selective catalytic reduction (SCR) of nitrogen oxides and a preparation method thereof. Background Art

[0002] Ceramic filter tube catalyst is a filter tube with both filtering and catalytic functions. The general method of manufacturing it is to use the inner and outer walls and internal space of the ceramic filter tube as the substrate, and load the carrier material in the substrate through various methods such as precipitation, impregnation, and spraying. The carrier usually contains at least one inorganic metal oxide. The carrier provides a porous, high surface area layer, which is bonded to the surface of the substrate after drying and calcination. The catalytically active material or its precursor is deposited on the carrier after impregnation of the substrate. Finally, the active component is formed by high-temperature calcination.

[0003] CN 114682250 A discloses a step-by-step preparation method for a ceramic fiber filter tube catalyst, wherein the ceramic fiber filter tube is impregnated with a solution containing an inorganic titanium source, an organic titanium source, and a manganese source and / or a vanadium source, dried in steps, and calcined in steps, and the four steps are repeated to obtain a ceramic fiber filter tube simultaneously loaded with large particles, small particles of titanium dioxide and active components, wherein the inorganic titanium source is selected from at least one of titanium sulfate, metatitanic acid and titanium tetrachloride, and the organic titanium source is selected from at least one of titanium isopropoxide, tetrabutyl titanate ethanol and polytitanium oxide. The organic titanium source is mixed with a solvent, and then an acid solution is added to the resulting mixture to obtain a coating slurry containing an organic titanium source, wherein the acid in the acid solution is selected from at least one of acetic acid, oxalic acid and hydrochloric acid. The method obtains a large particle size of titanium dioxide of 30 to 50 nm and a small particle size of titanium dioxide of 5 to 20 nm when a surfactant is added, and the pH range of the impregnation solution is not given, and it is impossible to draw a conclusion that the active components are uniformly distributed on the titanium dioxide carrier.

[0004] CN 104826490 A discloses a composite filter element and a preparation method thereof, wherein a sol is impregnated into a porous matrix to gel the sol in the porous matrix, and then the porous matrix is ​​heat-treated to convert the gel into nanoparticles, thereby forming a carrier layer, and then a catalytic active substance precursor solution is prepared and impregnated into the carrier, and a catalytic active layer is formed on the carrier layer after heat treatment. The method uses aluminum nitrate and butyl titanate, deionized water, alcohol and other acids mixed in a certain proportion, and the pH value is controlled between 2 and 4 by adjusting the acid content to form a sol to prepare a precursor solution of the carrier, and a step-by-step impregnation method is used to first prepare the carrier layer and then prepare the catalytic active layer, which cannot ensure the uniform distribution of the active components on the carrier. Existing ceramic catalysts of this type cannot ensure the uniform distribution of the active components on the carrier. Summary of the invention

[0005] The purpose of the present invention is to provide a ceramic filter tube catalyst and its preparation method and application, specifically a ceramic filter tube catalyst for selective catalytic reduction (SCR) of nitrogen oxides. The present invention realizes uniform distribution of catalytic components on the carrier, reduces the occurrence of agglomeration, and reduces the amount of catalytic components used.

[0006] In order to achieve the above purpose, the present invention adopts the following technical solutions:

[0007] In one aspect, the present invention provides a method for preparing a ceramic filter tube catalyst, comprising the following steps:

[0008] The carrier is added into water, and the precursor of the active component is added under stirring, and the stirring is continued to obtain a mixture;

[0009] Acid is added to adjust the pH value of the mixture to 4.0 to 4.5, and then a dispersant is added to adjust the pH value to 8.5 to 9.5;

[0010] grinding the mixture to a D50 particle size of 40 to 300 nm, and then diluting it with a dispersant solution to obtain a diluted impregnation solution;

[0011] The ceramic filter tube is immersed in the diluted impregnation solution, and then dried and calcined to obtain the ceramic filter tube catalyst.

[0012] The following is a detailed description of each step:

[0013] 1) Add the carrier into water, add the precursor of the active component under stirring, and continue stirring to obtain a mixture.

[0014] According to the preparation method of the present invention, this step is preferably: adding the carrier into water, stirring continuously for 2 to 3 hours, then adding the precursor of the active component under stirring, and continuing stirring for 2 to 3 hours to obtain the mixture.

[0015] According to the preparation method of the present invention, preferably, the mass ratio of water to carrier is 2.2-2.35:1; the mass ratio of the precursor of the active component to the carrier is 0.02-0.1:1.

[0016] According to the preparation method of the present invention, preferably, the carrier is titanium dioxide (TiO2).

[0017] According to the preparation method of the present invention, preferably, the titanium dioxide is selected from at least one of anatase, rutile and titanium dioxide; more preferably, the mass ratio of titanium dioxide in the anatase is ≥95wt%.

[0018] According to the preparation method of the present invention, preferably, the primary particle size D50 of the carrier is 20 to 200 nm; more preferably, 100 to 150 nm.

[0019] According to the preparation method of the present invention, preferably, the water is desalted water.

[0020] According to the preparation method of the present invention, preferably, the precursor of the active component includes ammonium metavanadate; more preferably, it further includes ammonium metatungstate and / or ammonium heptamolybdate. The active component in the corresponding prepared ceramic filter tube catalyst includes vanadium pentoxide (V2O5), and more preferably, it also includes tungsten trioxide (WO3) and / or molybdenum trioxide (MoO3). When the active component contains tungsten trioxide (WO3) and / or molybdenum trioxide (MoO3), according to the denitrification efficiency, sulfur resistance and service life, the main component is still mainly V, and other components are added as auxiliary.

[0021] 2) Acid is added to adjust the pH value of the mixture to 4.0-4.5, and then a dispersant is added to adjust the pH value to 8.5-9.5.

[0022] According to the preparation method of the present invention, preferably, an acid is added to adjust the pH value of the mixture to 4.0-4.5, and stirring is continued for 5-10 hours after the pH stabilizes to keep the surface charge of the active component negative and the Zeta potential of the carrier positive, and by changing the pH value, the charged particles adsorb the oppositely charged particles in the dispersed system, and the active components are gradually deposited or adsorbed onto the surface of the carrier.

[0023] According to the preparation method of the present invention, preferably, the acid is selected from at least one of nitric acid, formic acid, acetic acid and citric acid.

[0024] According to the preparation method of the present invention, the dispersant is added to adjust the pH value to 8.5 to 9.5. Preferably, the dispersant is selected from at least one of ethylamine, propylamine and butylamine.

[0025] Adding a dispersant can prevent the carrier from agglomerating, prevent agglomeration, destroy the agglomerates that have been formed, etc. In order to better achieve a monolayer deposition of the active component on the surface of the carrier and achieve a high degree of dispersion of the active component. The addition of a dispersant will cause the pH of the impregnation solution to increase. In the range of 4 to 4.5, the metal ions of the carrier and the active component have opposite surface charges. In this pH range, the electrostatic attraction between metal compounds of opposite charges is used to bind the metal ions in a finely dispersed form on the surface of the carrier with opposite charges. After a period of time, equilibrium is reached. At this time, a dispersant is added, and the pH is raised to the range of 8.5 to 9.5. The optimal result of the combined use of balanced deposition and dispersants can be achieved. Before the pH is raised, there are still free metal ions and agglomerated carriers. According to the principle of chemical equilibrium movement, the increase in pH breaks the possible stable (equilibrium) phase of the water electrochemical system, allowing more metal ions to bind to the carrier sites, maximizing the metal ion loading efficiency, reducing the amount of active components used and the loading amount, and playing a role in cost saving.

[0026] 3) The mixture is ground to a D50 particle size of 40 to 300 nm, and then diluted with a dispersant solution to obtain a diluted impregnation solution.

[0027] In this step, the mixture is ground to a particle size of 40 to 300 nm, and the mixture of water, oxide and dispersant is changed from a suspension or dispersion (depending on the initial average particle size D50) to a colloidal system, i.e., an impregnation solution; it is then diluted with a dispersant solution to obtain a diluted impregnation solution.

[0028] According to the preparation method of the present invention, preferably, the dispersant solution is used to dilute the carrier and the active component precursor to a total mass concentration of about 10 wt %, such as 10.5 wt % to 11.7 wt %.

[0029] According to the preparation method of the present invention, preferably, the mass concentration of the dispersant solution is 0.10% to 0.20%, such as 0.10% to 0.20% ethylamine solution, 0.10% to 0.20% 1-propylamine solution, 0.10% to 0.20% 2-aminopropane solution, etc. The solvent in the preparation method of the present invention is water, so the solvent of the dispersant solution is also water.

[0030] According to the preparation method of the present invention, preferably, a surfactant is added at the same time when the dispersant solution is diluted. Adding a surfactant to the diluted impregnation solution increases fluidity to a certain extent, facilitates impregnation into the gaps of the ceramic filter tube, and can reduce the impregnation time.

[0031] According to the preparation method of the present invention, preferably, during the dilution process, the surfactant is added dropwise, and then stirring is continued for 4 to 6 hours.

[0032] According to the preparation method of the present invention, preferably, the surfactant is added in an amount of 0.3 wt% to 1.4 wt% of the mass of the carrier. More preferably, the surfactant is added in an amount of 0.3 wt% to 0.5 wt% of the mass of the carrier and the active component precursor.

[0033] According to the preparation method of the present invention, preferably, the surfactant is selected from at least one of sodium fatty alcohol polyoxyethylene ether sulfate, sodium coconut alcohol polyoxyethylene ether alcohol sulfonate, and sodium hexadecyl aryl sulfonate.

[0034] 4) Soaking the ceramic filter tube in the diluted impregnation solution, and then drying and calcining to obtain the ceramic filter tube catalyst.

[0035] In the present invention, the ceramic filter tube serves as a substrate on which the catalyst carrier and the active components are supported.

[0036] According to the preparation method of the present invention, preferably, the soaking time is 18 to 24 hours.

[0037] According to the preparation method of the present invention, preferably, the drying temperature is 150-200° C., and the time is 4-8 h; more preferably, the drying temperature is 200° C., and the time is 4-8 h.

[0038] According to the preparation method of the present invention, preferably, the calcination temperature is 400-450° C. and the calcination time is 4-8 hours.

[0039] Another aspect of the present invention provides a ceramic filter tube catalyst, which is obtained by any of the above preparation methods.

[0040] The ceramic filter tube catalyst comprises a ceramic filter tube substrate and a coating, wherein the coating comprises a carrier and an active component, wherein the active component is adsorbed on the surface of the carrier.

[0041] According to the ceramic filter tube catalyst of the present invention, preferably, the carrier is titanium dioxide. More preferably, the titanium dioxide is selected from at least one of anatase, rutile and titanium dioxide; more preferably, the mass ratio of titanium dioxide in the anatase is ≥95wt%.

[0042] The titanium dioxide carrier is composed of single or agglomerated nanoparticles of titanium dioxide, and its primary particle size D50 is preferably 20 to 200 nm, and more preferably 100 to 150 nm.

[0043] According to the ceramic filter tube catalyst of the present invention, preferably, the active component includes vanadium pentoxide (V2O5), and more preferably further includes tungsten trioxide (WO3) and / or molybdenum trioxide (MoO3).

[0044] According to the ceramic filter tube catalyst of the present invention, preferably, in the ceramic filter tube catalyst, the mass ratio of metal vanadium to metal titanium is 0.12 to 0.2.

[0045] In another aspect, the present invention provides one or more ceramic filter tube catalysts for use in selective catalytic reduction (SCR) of nitrogen oxides.

[0046] The present invention mixes the carrier with the active component carrier to obtain a mixture, and then adjusts the pH value so that the surface charge of the active component is negative and the Zeta potential of the carrier is positive, so that the oppositely charged particles in the charged particle adsorption system gradually deposit or adsorb the active component on the surface of the carrier. The present invention utilizes the electrostatic attraction between oppositely charged metal compounds to combine a metal compound on the surface of the oppositely charged metal compound in a finely dispersed form, which can achieve high dispersion and monolayer coverage of the active component on the carrier, avoid forming excessive crystalline catalytic active substances on the carrier, thereby reducing the amount of active component used without affecting the activity of the catalyst. At the same time, the reduction of active components leads to a reduction in SO2 oxidation, which will reduce the formation of ammonium bisulfate (ABS).

[0047] The ceramic filter tube catalyst of the present invention has the function of selective catalytic reduction (SCR) of nitrogen oxides, and its preparation method is novel and simple to implement. The uniform distribution of the catalytic components in the carrier layer is achieved by regulating the pH value, thereby reducing the amount of catalytically active components and lowering the use cost. DETAILED DESCRIPTION

[0048] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0049] All numerical specifications herein (e.g., temperature, time, concentration, and weight, etc., including ranges for each thereof) are generally approximate values ​​that may be appropriately varied (+) or (-) in increments of 0.1 or 1.0. All numerical specifications may be understood as being preceded by the term "about."

[0050] Example 1

[0051] This embodiment prepares a ceramic filter tube catalyst, including the following steps:

[0052] 1) 8.5 kg of anatase titanium dioxide (anatase titanium dioxide content of 95 wt%, primary particle size D50 between 100 and 150 nm) was added to 19 kg of deionized water and stirred continuously for 2 h; then 1.74 kg of ammonium metavanadate and 0.42 kg of ammonium metatungstate were added under stirring and stirring was continued for 2 h.

[0053] 2) While stirring, nitric acid was added to adjust the pH value to 4.2±0.1 until it was stable, and the slurry was stirred for 5 hours after stabilization; then ethylamine was added to adjust the pH value to 9.2±0.1 until it was stable to obtain a mixed solution.

[0054] 3) The mixed solution is placed in a ball mill and ground into a particle size of 90 to 110 nm (D50), and 69 L of 0.10% ethylamine solution is added for dilution; 0.05 kg of sodium hexadecyl aryl sulfonate is added dropwise during the dilution process, and the mixture is stirred for 4 hours to obtain a diluted impregnation solution; wherein the carrier exists in the impregnation solution in the form of small nanoparticles.

[0055] 4) The ceramic filter tube is immersed in the diluted impregnation solution for 24 hours, then dried at 200° C. for 8 hours, and calcined at 400° C. for 4 hours to obtain a molded product.

[0056] In the obtained catalyst, the V / Ti mass ratio was 0.17.

[0057] Example 2

[0058] This embodiment prepares a ceramic filter tube catalyst, including the following steps:

[0059] 1) 6.8 kg of anatase titanium dioxide (anatase titanium dioxide content of 99 wt%, primary particle size D50 between 150 and 200 nm) was added to 15 kg of deionized water and stirred continuously for 2 h. Subsequently, 1.97 kg of ammonium metavanadate, 0.48 kg of ammonium metatungstate and 0.2 kg of ammonium heptamolybdate were added and stirring was continued for 2 h.

[0060] 2) Add citric acid while stirring to adjust the pH value to 4.0±0.1 until it is stable, and continue to stir the slurry for 10 hours after it is stable; then add 1-propylamine to adjust the pH value to 8.5±0.1 until it is stable to obtain a mixed solution.

[0061] 3) The mixed solution is placed in a ball mill and ground into a particle size of 100-150 nm (D50), and 56 L of 0.10% 1-propylamine solution is added for dilution. During the dilution process, 0.09 kg of fatty alcohol polyoxyethylene ether sodium sulfate is added dropwise, and stirred for 4 hours to obtain a diluted impregnation solution; wherein the carrier exists in the form of nanoparticles in the impregnation solution.

[0062] 4) The ceramic filter tube was immersed in the diluted impregnation solution for 18 hours, then dried at 150° C. for 6 hours, and calcined at 420° C. for 6 hours to obtain a molded product.

[0063] In the obtained catalyst, the V / Ti mass ratio was 0.12.

[0064] Example 3

[0065] This embodiment prepares a ceramic filter tube catalyst, including the following steps:

[0066] 1) 9.9 kg of anatase titanium dioxide (anatase titanium dioxide content of 97 wt%, primary particle size D50 between 50 and 100 nm) was added to 22 kg of deionized water and stirred continuously for 2 h; then 2.35 kg of ammonium metavanadate, 0.45 kg of ammonium metatungstate and 0.3 kg of ammonium heptamolybdate were added and stirred for 2 h.

[0067] 2) Under continuous stirring, acetic acid was added to adjust the pH value to 4.5±0.1 until it was stable, and the slurry was stirred for 8 hours after stabilization. Subsequently, 2-aminopropane was added to adjust the pH value to 9.5±0.1 until it was stable to obtain a mixed solution.

[0068] 3) The mixed solution is placed in a ball mill and ground into a particle size of 40 to 80 nm (D50), and 80 L of 0.10% 2-aminopropane solution is added for dilution. During the dilution process, 0.03 kg of sodium coconut oil polyoxyethylene ether alcohol sulfonate is added dropwise, and stirred for 4 hours to obtain a diluted impregnation solution; wherein the carrier exists in the impregnation solution in the form of small nanoparticles.

[0069] 4) The ceramic filter tube is immersed in the diluted impregnation solution for 20 hours, then dried at 180° C. for 4 hours, and calcined at 450° C. for 8 hours to obtain a molded product.

[0070] In the obtained catalyst, the V / Ti mass ratio was 0.2.

[0071] Comparative Example 1

[0072] This comparative example is carried out using the same materials as Example 1, except that a step-by-step impregnation method is used:

[0073] 1) 8.5 kg of anatase titanium dioxide (anatase titanium dioxide content of 95 wt%, primary particle size D50 between 100 and 150 nm) was added to 19 kg of demineralized water and stirred continuously for 2 h; then the ceramic filter tube was immersed in the solution for 18 h, then dried at 200 ° C for 6 h, and calcined at 420 ° C for 6 h to obtain an intermediate product.

[0074] 2) Add 1.74 kg of ammonium metavanadate and 0.42 kg of ammonium metatungstate into 19 kg of deionized water and stir for 2 hours; immerse the intermediate product in the solution for 18 hours, then dry at 200° C. for 6 hours, and calcine at 420° C. for 6 hours to obtain the final molded product.

[0075] The denitrification activities of the three example samples and the comparative example samples were evaluated under laboratory simulated flue gas conditions.

[0076] Simulated smoke test conditions:

[0077] NO: 500ppm, NH3: 500ppm, O2: 6%, H2O: 10%, SO2: 100ppm;

[0078] The test temperatures are 200°C, 250°C, 300°C and 350°C respectively.

[0079] The evaluation results are shown in Table 1 below.

[0080] Table 1

[0081]

[0082] From the results in Table 1, it can be seen that the catalyst prepared by the present invention has a denitration efficiency of more than 85% in the temperature range of 200-350°C; while the catalyst prepared by the traditional process of stepwise impregnation of active coating in the tube wall of the ceramic filter tube has a poor denitration effect.

[0083] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing a ceramic filter tube catalyst, wherein: The preparation method comprises the following steps: The carrier is added into water, and the precursor of the active component is added under stirring, and the stirring is continued to obtain a mixture; Acid is added to adjust the pH value of the mixture to 4.0 to 4.5, and then a dispersant is added to adjust the pH value to 8.5 to 9.5; grinding the mixture to a D50 particle size of 40 to 300 nm, and then diluting it with a dispersant solution to obtain a diluted impregnation solution; The ceramic filter tube is immersed in the diluted impregnation solution, and then dried and calcined to obtain the ceramic filter tube catalyst.

2. The preparation method according to claim 1, wherein The mass ratio of water to carrier is 2.2-2.35:1; The mass ratio of the precursor of the active component to the carrier is 0.02-0.1:

1.

3. The preparation method according to claim 1, wherein The carrier is titanium dioxide.

4. The preparation method according to claim 1, wherein The precursor of the active component includes ammonium metavanadate.

5. The preparation method according to claim 4, wherein The precursor of the active component also includes ammonium metatungstate and / or ammonium heptamolybdate.

6. The preparation method according to claim 1, wherein an acid is added to adjust the pH value of the mixture to 4.0-4.5, and stirring is continued for 5-10 hours after the pH value stabilizes.

7. The preparation method according to claim 1, wherein The acid is selected from at least one of nitric acid, formic acid, acetic acid and citric acid.

8. The preparation method according to claim 1, wherein The dispersant is selected from at least one of ethylamine, propylamine and butylamine.

9. The preparation method according to claim 1, wherein The dispersion is diluted with a dispersant solution until the total mass concentration of the carrier and the active component precursor is 10.5 wt % to 11.7 wt %.

10. The preparation method according to claim 1, wherein: When diluting with the dispersant solution, a surfactant is added at the same time; the added amount of the surfactant is 0.3wt% to 1.4wt% of the mass of the carrier.

11. The preparation method according to claim 10, wherein: The surfactant is selected from at least one of sodium fatty alcohol polyoxyethylene ether sulfate, sodium coconut alcohol polyoxyethylene ether alcohol sulfonate and sodium hexadecyl aryl sulfonate.

12. The preparation method according to claim 1, wherein: The soaking time is 18 to 24 hours.

13. The preparation method according to claim 1, wherein The drying temperature is 150-200° C. and the drying time is 4-8 hours.

14. The preparation method according to claim 1, wherein: The calcination temperature is 400-450° C. and the calcination time is 4-8 hours.

15. A ceramic filter tube catalyst obtained by the preparation method according to any one of claims 1 to 14, wherein: The ceramic filter tube catalyst comprises a ceramic filter tube substrate and a coating, wherein the coating comprises a carrier and an active component, wherein the active component is adsorbed on the surface of the carrier.

16. The ceramic filter tube catalyst according to claim 15, wherein: In the ceramic filter tube catalyst, the mass ratio of metal vanadium to metal titanium is 0.12 to 0.

2.

17. Use of the ceramic filter tube catalyst according to any one of claims 15 to 16 in the selective catalytic reduction of nitrogen oxides.

Citation Information

Patent Citations

  • Composite filter core element and production method thereof

    CN104826490A